Ornamen Flora Teknik Kolase pada Toples Makanan Berbahan Stiker Berdasarkan Prinsip-Prinsip Seni Rupa - Rahmita Ilmi; Azmi Azmi (Mahesa Research Center, 2021)
This study aims to see the ability of students to apply decorative styles with the collage technique made from stickers in class VII SMP Negeri 1 Perbaungan based on the principles of fine arts, namely unity, balance, and rhythm. The theme used is flora with food jars as media. Based on the researchers 'initial observations, the students' decorative works using paint on paper media were still not optimal. As well as the lack of student knowledge in applying the principles of fine arts is a factor driving student work to be less than optimal. The population in this study was all class VII students of SMP Negeri 1 Perbaungan with 277 students. The sample was 21 students of class VII-1 (superior) using the purposive sampling technique. This study used the descriptive qualitative method. The findings of this study indicate that, in total, the application of the ornamental variety of class VII-1 collage techniques based on the principles of unity, balance, and rhythm has an average value of = 79.5 with a reasonably good category. In detail, the average value is based on the following three aspects: unity = 79.7 (good enough), balance = 79.5 (good enough), and rhythm = 79.3 (good enough) with performance indicators: unity, balance, and rhythm.